Effects of Knowledge Acquisition, Information Capability and Relationship Quality on Product Innovation Flexibility Among Manufacturing Firms in Malaysia - Vani Malasamy, Gogila; Nadarajah, Devika; Adal Mehmood, Sultan (International Journal of Engineering and Technology, 2018)
Knowledge management is the process of identifying, creating, assimilating and applying corporate knowledge to take advantage of new opportunities and enhance organizational performance. It involves both internal and external organizational capabilities. This study focuses on information capability, knowledge acquisition and relationship quality as capabilities pertinent to organisations aiming to achieve greater product innovation flexibility. Understanding and improving product innovation flexibility is crucial in the context of Malaysia in order to enable the nation to be at par with other countries enjoying better knowledge capital. Central tenets in building knowledge capital are creativity and innovation. The study is carried out in the manufacturing arena specifically on Electrical and Electronics (E&E) subsector as this subsector has achieved remarkable growth and has significant influence over the Malaysian economy. Quantitative research method using survey instrument was adopted in this study. Interestingly, the findings from this study revealed only knowledge acquisition and relationship quality as having significant relationship with product innovation flexibility. The findings are important to research and practice. Firms setting out to improve product innovation flexibility should pay careful attention to knowledge acquisition and relationship quality.Â Â